Photoacoustic and EPR studies of two copper(II) complexes with spermine analogues - Guskos, N.; V. Likodimos; Typek, J.; Maryniak, M.; Grech, E.; Kolodziej, B. (Reviews on Advanced Materials Science, 2007)
Two polyamine copper(II) compounds of spermine analogues: Cu[H2N(CH2)3NH (CH2)2NH(CH2)3NH2] (ClO4)2 (abbreviated as Spc323) and Cu[H2N(CH2)3NH (CH2)3NH(CH2)3NH2] (ClO4)2 (abbreviated as Spc333) have been synthesized and characterized by spectroscopic methods. The electron paramagnetic resonance (EPR) and photoacoustic spectroscopies have been used for studying CU2+ d-d transitions. The EPR spectra of copper(II) ions in both complexes have displayed a different crystal field symmetry: orthorhombic for Spc323 complex, and axial, with the hyperfine interaction, for Spc333 complex. In the visible region of electromagnetic radiation the photoacoustic absorptions from the d-d electron transitions with different energies and linewidths have been observed. Comparison of the obtained results is made with previous measurements on similar spermine compounds. © 2007 Advanced Study Center Co. Ltd.
cited By 3